TA'LIL AL-AHKAM DALAM PENGEMBANGAN EKONOMI ISLAM: STUDI LITERATUR TENTANG RASIONALISASI HUKUM DAN APLIKASI MAQASID AL-SHARIAH - Dewi Risyantika; Moh. Bahrudin; Syamsul Hilal (NATUJA: Jurnal Ekonomi Syariah, 2025)
Ta'lil al-ahkam (legal reasoning through the identification of cause or rationale) is a critical methodological framework for understanding the adaptation of Islamic law to the complex and multifaceted challenges of contemporary economics. This article employs the library research methodology to examine the role of ta'lil al-ahkam in developing Sharia-compliant financial instruments and addressing increasingly intricate modern economic issues. Through a systematic analysis of legal texts, peer-reviewed journal articles, and regulatory documents from the National Sharia Board-Indonesian Ulema Council (DSN-MUI), this study identifies that ta'lil al-ahkam functions as a crucial bridge between classical Islamic jurisprudence and contemporary economic practice. The findings indicate that although ta'lil al-ahkam has successfully facilitated the creation of innovative Sharia-compliant products such as sukuk, Islamic fintech, and Islamic banking instruments, substantive questions remain regarding whether these applications adequately reflect the maqasid al-shariah emphasis on economic justice, social welfare, and inclusive empowerment. This study concludes that the effective integration between maqasid-based ta'lil al-ahkam is essential to ensure that the development of Islamic economics serves the genuine objective of maslahah (welfare) and promotes sustainable development that benefits all segments of society.